Experimental Study on Chemotherapy of Acute Glanders - V. I. Ilyukhin; K. A. Rotov; T. V. Senina; E. A. Snatenkov; S. N. Tikhonov; N. G. Plekhanova; A. S. Kulikova; E. V. Shubnikova; E. V. Korol; M. O. Nekhezina (Антибиотики и Химиотерапия)
Glanders is a zoonotic infection inducing acute forms of the disease (pneumonia, sepsis) in humans and animals under certain conditions, which even with the use of modern chemotherapy have unfavourable prognosis. Insufficient of efficacy of antibiotics with in vitro low MIC for planktonic bacterial suspension of Burkholderia mallei in chemotherapy of acute forms of glanders was due to the capacity of the pathogen for intracellular survival and formation of biofilms. Under such conditions the susceptibility of B.mallei to antibiotics lowered by several orders of magnitude. Chemotherapy of the glanders acute forms in animals usually provided only an increase of the lifespan, while among the survivors there was recorded a high relapse rate. More favourable outcomes were observed with the use of in vitro effective antibiotics in the form of clathrate compounds or especially liposomal forms. In the experiments with golden hamsters the survival rate reached 100% in 1000 Dlm infection even with the treatment onset by meropenem liposomal form 48 hours after the infection. Chemotherapeutics in the liposomal form significantly lowered resistance of B.mallei in both the experiments with a suspension of planktonic organisms and the use of bacteria interned in eukaryotic cells (Tetrahymena pyriformis).